Organic derivatives of Mg(BH4)2 as precursors towards MgB2 and novel inorganic mixed-cation borohydrides12. Issue 36 (22nd August 2016) - Wegner, W.; Jaroń, T.; Dobrowolski, M. A.; Dobrzycki, Ł.; Cyrański, M. K.; Grochala, W.
Abstract : A series of organic and inorganic derivatives of magnesium borohydride have been prepared and thoroughly characterized. Abstract : A series of organic derivatives of magnesium borohydride, including Mg(BH4 )2 ·1.5DME (DME = 1, 2-dimethoxyethane) and Mg(BH4 )2 ·3THF (THF = tetrahydrofuran) solvates and three mixed-cation borohydrides, [Cat]2 [Mg(BH4 )4 ], [Cat] = [Me4 N], [ n Bu4 N], [Ph4 P], have been characterized. The phosphonium derivative has been tested as a precursor for synthesis of inorganic mixed-metal borohydrides of magnesium, M x [Mg(BH4 )2+ x ], M = Li–Cs, via a metathetic method. The synthetic procedure has yielded two new derivatives of heavier alkali metals M3 Mg(BH4 )5 (M = Rb, Cs) mixed with amorphous Mg(BH4 )2 . Thermal decomposition has been studied for both the organic and inorganic magnesium borohydride derivatives. Amorphous MgB2 has been detected among the products of the thermal decomposition of the solvates studied, together with organic and inorganic impurities.